2020
DOI: 10.5539/jas.v12n11p223
|View full text |Cite
|
Sign up to set email alerts
|

Organic Inputs and Chemical Fertilizer on Carbon Mineralization From Two Ultisols

Abstract: There are challenges that limit the use of organic inputs for soil fertility management. Amongst them is the limited knowledge of factors that affect rates of decomposition and nutrient release from different organic inputs. A study was conducted on surface soil samples of two Ultisols to determine factors affecting carbon (C) mineralization from selected organic inputs. A loamy sand (LS) from a Kandiustult and a sandy clay loam (SCL) from a Paleustult were used. Fine earth fractions of the soils mixed with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…These results corroborate findings by Bhat et al (2015) who established that application of organic inputs either alone or in combination with chemical fertilizers resulted in 19% to 73% more N o than the control and 11% to 57% more N o than conventional treatments. The results further support findings by Kalala, Shitumbanuma, Adamtey and Benson (2020) who, working with the same soils and same inputs used in this study, established that the addition of organic inputs with or without chemical fertilizer resulted in higher carbon emissions ranging from 81 to 129% and 18 to 34% than control treatments on LS and SCL soils respectively.…”
Section: Effect Of Organic Inputs On Nitrogen Mineralizationsupporting
confidence: 90%
See 2 more Smart Citations
“…These results corroborate findings by Bhat et al (2015) who established that application of organic inputs either alone or in combination with chemical fertilizers resulted in 19% to 73% more N o than the control and 11% to 57% more N o than conventional treatments. The results further support findings by Kalala, Shitumbanuma, Adamtey and Benson (2020) who, working with the same soils and same inputs used in this study, established that the addition of organic inputs with or without chemical fertilizer resulted in higher carbon emissions ranging from 81 to 129% and 18 to 34% than control treatments on LS and SCL soils respectively.…”
Section: Effect Of Organic Inputs On Nitrogen Mineralizationsupporting
confidence: 90%
“…The composted cattle manure, despite having a relatively lower C/N ratio, had one of the lowest %N min which was significantly lower than all the other organic inputs on the SCL. This, as stated by Kalala et al (2020) could be as a result of the presence of more recalcitrant carbon as most of the labile carbon might have been removed during the composting process.…”
Section: Effect Of Organic Inputs On Nitrogen Mineralizationmentioning
confidence: 96%
See 1 more Smart Citation
“…There was probably significant leaching of nutrients at Misamfu because of the sandy nature of the soils and the high rainfall at Misamfu. Kalala et al (2020) reported high seasonal organic matter decomposition rates of about 10.3% on the highly permeable sandy soils at Misamfu. A combination of high organic matter decomposition rates and high rainfall are conducive to high rates of leaching of nutrients.…”
Section: Effect Of Organic Amendments On Maize Grain Yieldmentioning
confidence: 97%
“…The agro-ecological conditions at Msekera were probably better suited for the use of Tephrosia vogelii and pigeon pea for improving maize production than at Misamfu. According to Kalala et al (2020), the loamy soils at Msekera had seasonal organic matter decomposition rates of about 4.9% compared to the high rates of about 10.3% observed on the sandy soils at Misamfu. The combination of the higher rainfall at Misamfu and high organic matter decomposition rates on soils with high permeability and low nutrient retention may have resulted in greater leaching of nitrogen and other nutrients at Misamfu compared to Msekera.…”
Section: Effect Of Organic Amendments On Maize Grain Yieldmentioning
confidence: 97%